Long haul COVID-19 and its associated risk factors: a systematic review and meta-analysis protocol - Agarwal, Monika; Pandit, Pratyaksha; Khan, Maviya; Jauhari, Sugandha; Singh, Abhishek; Verma, Smriti (International Journal Of Community Medicine And Public Health, 2023)
COVID-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2) first reported in December 2019 in Hubei province of Wuhan, China. Most people infected with COVID-19 disease experienced mild to moderate symptoms or even no symptoms at all, but growing body of evidence has shown that large number of COVID-19 survivors are experiencing multitude of long-lasting symptoms persisting for varied number of periods after the acute phase of infection. This condition is known as long COVID and since July 2021 has been added as a recognized condition that could result in a disability under the American with disability act (ADA). We will undertake a systematic search in PubMed, PubMed Central and Google scholar from December 2019 till June 2022. The study designs to be included will be cross-sectional, case-control, cohort, follow-up, observational studies. No ethical issues are anticipated. Dissemination will be done by submitting article to academic peer review journals. To add into the pool of knowledge of long COVID and provide evidence-based insight, this systematic review was planned to know about the prevalence of long COVID sequalae, commonly reported symptoms by COVID-19 survivors at an interval of 3, 6 and 12 months and possible risk factors attributable to the emergence of these symptoms. PROSPERO registration (CRD 42022340175).